Dating the Hand-copying of the Heart Sutra Annotation from the Dunhuang Museum Collection - Zhang, Yongquan (Studies in Chinese Religions, 2021)
Dunhuang Document #77 in the collection of the Dunhuang Museum includes five Chan texts including the Platform Sutra, and is included in the first edition of the Catalogue of National Precious Antique Books by the Chinese government. This manuscript has been dated to the period of the Guiyi Circuit 歸義軍 (848–1035 CE). The present study points out that Zhu Xin jing (Heart Sutra Annotation) by Shi Jingjue 釋淨覺, which was copied after the other four texts (such as the Platform Sutra), differs from them, and that this text is quite possibly a copy during or after the Yuan dynasty (1271–1368 CE). The manuscript of the Zhu Xin jing not only differs from the other four in terms of handwriting, ordering, and marks for indicating the titles. It also presents a number of popular characters which are rarely or never seen in credible Dunhuang manuscripts. These characters were largely produced during the Song or even Yuan dynasties. The present study infers that the Zhu Xin jing was not from the Mogao library cave, but quite possibly was added by someone during or after the Yuan dynasty, or even by a modern person.